Decentralization and Local Governance in MENA : A Survey of Policies, Institutions, and Practices - World Bank (World Bank, Washington, DC, 2014)
Entering the 21st century, the 1999-2000 World Development Report (WDR), identifies two main forces that are shaping the world in which development policy is being defined and implemented: (i) globalization, the increasing worldwide integration of private sector interaction and commercial relationships; and (ii) localization, a process of devolving fiscal and administrative roles and responsibilities from central to sub-national tiers of government. It goes on to note that these global-private and local-public pressures are not only reinforcing, but also challenging traditional paradigms and forms of intergovernmental systems. Political decentralization, often associated with pluralistic politics and representative government, aims to give citizens more say in public policy and decision-making. Its advocates assume that decisions made with greater participation will be better informed and more relevant to diverse interests in society than those made only by national political authorities. The concept implies that the selection of representatives from local electoral jurisdictions allows citizens to know better their political representatives and allows elected officials to know better the needs and desires of their constituents. Administrative decentralization aims to redistribute authority, responsibility and financial resources for providing public services among different levels of government. It typically takes three forms: de-concentration, delegation and devolution. Fiscal decentralization vests greater autonomy and authority with local governments in matters of fiscal importance, empowering local governments to generate their own revenues, through taxes and user charges, as well as determining their expenditure priorities based on a clear assignment of functions and responsibilities. Over the last two decades, it has been estimated that more than 100 countries, most of them in the developing world, have experimented with various forms of decentralization.